Design and implementation of a general software library for using NSGA-II with SWAT for multi-objective model calibration. (October 2016) - Ercan, Mehmet B.; Goodall, Jonathan L.
Abstract: Calibrating watershed-scale hydrologic models remains a critical but challenging step in the modeling process. The Soil and Water Assessment Tool (SWAT) is one example of a widely used watershed-scale hydrologic model that requires calibration. The calibration algorithms currently available to SWAT modelers through freely available and open source software, however, are limited and do not include many multi-objective genetic algorithms (MOGAs). The Non-Dominated Sorting Genetic Algorithm II (NSGA-II) has been shown to be an effective and efficient MOGA calibration algorithm for a wide variety of applications including for SWAT model calibration. Therefore, the objective of this study was to create an open source software library for multi-objective calibration of SWAT models using NSGA-II. The design and implementation of the library are presented, followed by a demonstration of the library through a test case for the Upper Neuse Watershed in North Carolina, USA using six objective functions in the model calibration. Highlights: We present an open-source software library for calibration of SWAT models. The library implements the NSGA-II multi-objective genetic algorithm. The library is used to calibrate a SWAT model of the Upper Neuse Watershed, NC. The library can be used within SWAT-CUP for data visualization.